Modernization of irrigation systems: measures to reduce pressure on water demand in Lebanon - Karaa K.; Karam F.; Raad R. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
In Lebanon, water balance will reach its limits by 2020. Agriculture sector is the main consumer of water (around 70 percent of the total needs). In order to support water saving, the Lebanese government is applying a long term plan aimed at rehabilitating and modernizing the water sector. The policy adopted includes a number of strategies: institutional reforms, new legislation and administrative structure, application of an integrated water management plan, rehabilitation of existing schemes, water storage capacity improvement. This policy must be completed and further actions should be envisaged. The application of this new policy is encountering many difficulties which need to be solved. The present paper aims to give an overview of these problems considering some case studies and to outline the measures that should be adopted in order to improve water use efficiency. Many recommendations are given but the involvement of farmers in the processes, through water user associations, is still the main goal to achieve in order to obtain significant results.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)